The Position of Panai' Money in the Marriage of the Bugis-Makassar Societ: Fatwa Analysis of the Indonesian Ulema Council of South Sulawesi Province - Qayyum, Abdul Rahman; Lanta, Zulkifli; Ramadhan, Muh Ardin Abizal (Parewa Saraq: Journal of Islamic Law and Fatwa Review, 2023)
The tradition of panai’ money in South Sulawesi is a form of respect from the party who proposes (men) to women as a form or process of family ties. The main point of this study is how the Position of panai’ Money in the Marriage of the Bugis-Makassar Tribe Community; Fatwa Study of the Indonesian Ulema Council of South Sulawesi Province. This study aims to analyze the fatwa issued by the Indonesian Ulema Council of South Sulawesi Province regarding panai’ money in the marriage tradition of the Bugis-Makassar community. The type of research used in this study is qualitative descriptive research that provides an overview of phenomena and events that occur in a research location based on environmental conditions. The data used in this study are primary data and secondary data that are processed and presented to conclude. The results showed that the position of this panai’ money is a condition in a marriage because if there is no panai’ money then the marriage cannot be done. Islam does not regulate the provision of panai’ money but the law is good, Islam does not prohibit panai money in marriages of the Makassar bugis tribe because no evidence regulates it. Therefore, the MUI in its fatwa states that the law of this panai’ money is mubah, and if it does not burden both parties. The MUI in its fatwa does not state how much must be spent, because it adjusts to everyone's economic conditions.